Terceira onda do café: base conceitual e aplicações - Guimarães, Elisa Reis (2016)
It is considered that there are three movements, also called "waves", influencing the global coffee market and consumption. Each one features a diversified set of priorities and philosophies, causing such movements to coexist and sometimes overlap or "overflow", influencing the next “wave”. Thus, this paper was built in two stages. At first, the aim was to define, in a comprehensively and scientifically way, the concept of coffee’s Third Wave, which still has a vague definition and varied meanings for the several links in this chain, in order to establish a conceptual framework to facilitate the discussion and construction of new scientific knowledge regarding this theme. It was used extensive bibliographic research in academic and non-academic materials, combined with a categorical and qualitative content analysis. In the second stage, the aim was to answer the question: how is the Third Wave adopted in Brazil and in Minas Gerais and what are the main opportunities and challenges to the expansion of this movement at national and state level? Therefore, were conducted structured interviews with seven coffee experts, as well as semi-structured interviews with owners of three Minas Gerais’ coffee shops based on the concept of coffee’s Third Wave. In the first stage, the First, Second and Third waves were divided, respectively, in three, four and six categories, representing their most discussed topics, as well as were established twenty points of difference between the three waves. These results allowed us to understand the Third Wave as a movement in the specialty coffee market, characterized by significant change in the perception of the product, which is now considered equally or more complex than wine, seasonal, unique, singular, and ruled by the search and joint effort for exceptional quality in all stages of the supply chain, from the production of the beans to final consumption of the drink. To that end, several practices, widely discussed in this paper, are adopted. In the second stage, it was concluded that, although delayed, the adoption of the Third Wave in Brazil and in Minas Gerais is similar to the rest of the world, with only a few cultural differences, with great potential for expansion, but also some challenges, especially linked to the already established culture of commodity coffee consumption. Regarding the study of adoption by Minas Gerais state coffee shops, there was great adherence to the principles of this movement, but with the adoption of two different postures/attitudes, of purism and transition.